Implementasi Pembelajaran Kooperative Tipe Students Team Achievement Division (STAD) untuk Meningkatkan Kemampuan Berpikir Kritis dan Pemahaman Konsep - Mamil Gemilang (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This objective was to know: The implementation of STAD type cooperative learning to improve critical thinking skills and understand students' concepts in addictive substances and psychotropic substances. The population and sample consisted of two classes, namely the experimental class and the control class, each of which consisted of 35 students. The results of the research are: The implementation of STAD type cooperative learning in improving critical thinking skills and understanding the concepts of students who run conducive in accordance with the planned learning steps. The response of students to the implementation of STAD type of cooperative learning on addictive substances and psychotropic substances was quite enthusiastic, where all students seemed to be active during the learning process. The activities of the teacher teaching addictive substances and psychotropic substances using cooperative learning type STAD are very good in accordance with the learning indicators. Being in the critical thinking skills and mastery of students' concepts after learning using STAD type cooperative learning on addictive substances and psychotropic substances. Being in the critical thinking skills and mastery of students' concepts after learning using the lecture learning method on addictive substances and psychotropic substances. The development of an increase in students' critical thinking skills and conceptual mastery between classes using STAD type cooperative learning and classes using lecture learning methods on addictive substances and psychotropic substances, where the increase in the experimental class was higher than the control class.